Corruption In Indonesia (Form, Root Cause, Impact And Obstacles As Well As Strategies And Eradication Efforts) - Zatila , Fazia; Yandi, Rus (PT. NALURI EDUKASI PRESS, 2024)
Corruption cases are a problem that continues to occur in Indonesia. The dominant factor comes fromthe political elite who have positions in government. Corruption carried out by the state can harm thestate and harm the interests of many people. Law 31 of 1999 classifies corruption as follows:detrimental to the country's economy, bribery, embezzlement, extortion, fraud, procurement conflicts,complacency. Corruption has several dangerous consequences, namely threats to: national and statelife, development, state bureaucracy, the economic sector, health services, the political and democraticsector, and the social sector. Obstacles to eradicating corruption include obstacles: structural,cultural, instrumental and administrative factors that must be known in Indonesia. The factors thatcause corruption consist of 4 (four) aspects, namely: individual behavior, organization. Thiscommitment must be implemented as a comprehensive strategy to minimize the four aspects that causeit. corruption through strategies that include preventive and investigative. and repressive aspects thatare implemented intensively and addressed permanently, include: planning and restructuring publicservices, strengthening transparency, monitoring and sanctions, increasing the effectiveness ofsupporting tools for preventing corruption.